Frequency-dependent response of organic light-emitting diodes driven by DC and AC voltages. (1st September 2016) - Seo, Ji Dong; Oh, Jung Eun; Jo, Ho Keun; Kim, Hye Rim; Jang, Kyung Wook; Song, Min Jong; Kim, Tae Wan
ABSTRACT: In order to understand electrical and optical properties of the organic light-emitting diodes (OLEDs) driven by DC and AC voltages, characteristic frequency and RC equivalent circuit were investigated from the frequency-dependent response of the device. Luminance of the DC + AC driven OLED is less affected by frequency and waveforms (sine and square) of the AC voltage, and it is similar to that of the DC driven OLED. Unlike the AC driven OLEDs, the DC + AC driven OLEDs maintain the electroluminescent characteristics of the DC driven OLEDs. At low frequency of 40 Hz, a real part of impedance ( Z' ) above a turn-on voltage decreases exponentially with increasing voltage. Its behavior shows a similar pattern to a current flow of the DC driven OLEDs. As the frequency increases, a magnitude of resistive component ( Rp ) decreases and that of capacitive effect drastically increases. As the applied voltage increases, characteristic frequency exponentially increases. Application of the AC voltage with a proper frequency lower than the characteristic frequency to the device may reduce the accumulation of charge in the capacitive component ( Cp ) of RC equivalent circuit. Since this operation reduces a formation of space charge, it is expected to facilitate the charge transport.